Reversal of Epigenetic Silencing Allows Robust HIV-1 Replication in the Absence of Integrase Function - Ishak D. Irwan (American Society for Microbiology, 2020)
ABSTRACT Integration of the proviral DNA intermediate into the host cell genome normally represents an essential step in the retroviral life cycle. While the reason(s) for this requirement remains unclear, it is known that unintegrated proviral DNA is epigenetically silenced. Here, we demonstrate that human immunodeficiency virus 1 (HIV-1) mutants lacking a functional integrase (IN) can mount a robust, spreading infection in cells expressing the Tax transcription factor encoded by human T-cell leukemia virus 1 (HTLV-1). In these cells, HIV-1 forms episomal DNA circles, analogous to hepatitis B virus (HBV) covalently closed circular DNAs (cccDNAs), that are transcriptionally active and fully capable of supporting viral replication. In the presence of Tax, induced NF-κB proteins are recruited to the long terminal repeat (LTR) promoters present on unintegrated HIV-1 DNA, and this recruitment in turn correlates with the loss of inhibitory epigenetic marks and the acquisition of activating marks on histones bound to viral DNA. Therefore, HIV-1 is capable of replication in the absence of integrase function if the epigenetic silencing of unintegrated viral DNA can be prevented or reversed. IMPORTANCE While retroviral DNA is synthesized normally after infection by integrase-deficient viruses, the resultant episomal DNA is then epigenetically silenced. Here, we show that expression of the Tax transcription factor encoded by a second human retrovirus, HTLV-1, prevents or reverses the epigenetic silencing of unintegrated HIV-1 DNA and instead induces the addition of activating epigenetic marks and the recruitment of NF-κB/Rel proteins to the HIV-1 LTR promoter. Moreover, in the presence of Tax, the HIV-1 DNA circles that form in the absence of integrase function are not only efficiently transcribed but also support a spreading, pathogenic integrase-deficient (IN−) HIV-1 infection. Thus, retroviruses have the potential to replicate without integration, as is indeed seen with HBV. Moreover, these data suggest that integrase inhibitors may be less effective in the treatment of HIV-1 infections in individuals who are also coinfected with HTLV-1.